Production of Ho 2 O 3 and Dy 2 O 3 rare earth oxides doped selenium thin film and investigation of surface morphology and optical properties - Aydin, Handan; Kanca, M. Sait; Kok, Mediha; Tasgin, Yahya; Tatar, Beyhan (Elsevier Sci Ltd, 2024)
Thin film technology aims to improve and develop the properties of materials by coating technology. In this study, thin films consisting of rare earth element and selenium semiconductor material, which have recently been preferred in technological applications due to their important properties, are examined. Selenium thin films doped with Ho 2 O 3 and Dy 2 O 3 rare earth oxides (REO) were fabricated on glass substrate by thermal evaporation method. The surface morphology and optical properties of the thin films were investigated. As a result of surface morphology examinations, it was determined that homogeneous thin films were obtained and the thickness of the thin films varied between 20 and 30 mu m. In addition, the roughness value of the glass substrate decreased as a result of coating with doped selenium thin film. The band energy value obtained by UV-VIS measurements decreased compared to glass and was close to the selenium element value. In the comparison between selenium coatings doped with Ho 2 O 3 and Dy 2 O 3 , a notable reduction in the Eg value was observed specifically in the Ho 2 O 3 doped coatings.
Keywords: Thin film; Selenium; Glass substrate; Rare earth oxide; Band energy